ROI (Return on Investment) on Human Capital - Meparishvili, Ketevan (Caucasus Journal of Social Sciences, 2013)
In the 21st century, the success of proactive organization in no long-er evaluated by tangible assets like cash, plants, equipments and buildings. The outdated approach was quantifying the contribution of human resources in organization. For better presenting a real picture, a Human capital scorecard tool has been developed for measuring human resources contribution within the organization, which is innovation for Georgian business market. The topic is out-lining the main concepts, theories, hypothesis and application pro-cess of the Human capital evaluating tool, the primary goal of which is to measure financial and non-financial effects of investment and expenditures in human resources. By implementing relevant evalua-tion tool of human resources contribution within Georgian organiza-tions it means to acquire a value of understanding the human re-sources usefulness in company. By using the HR scorecard, manag-ers are able to determine what has affected the trend and forecast the future.